Is Structural and Cultural Iron Cage be a Barrier? A Study on Social Movement in Indonesia Electoral Democracy - Muliono (Political Sciences Program Study, 2024)
This study aims to discuss the social movements within the democratic process in Indonesia in 2024. This movement emerged as a response to injustice political policies in the context of electoral democracy that support president’ son be a vice president. His presence on the political arena is perceived by the public as a being laden with political dynasty values. Political dynasty itself is a threat for democracy. This study uses a qualitative approach, where primary data is obtained from observations and various reports revealed by various social media. This study shows that movement in various regions of Indonesia is a respond of public dissatisfaction and suspicion towards the dynastic power system. This study also reveals the dynamics of social movements in criticizing the government regime. Although this movement is massively carried out, there are very strong structural and cultural barriers, refers to Weber’s term this is alike an “iron cage”, and the social movement carried out have not yielded a significant results as needed by the public. This study concludes that social movements have their own dynamics and it is necessary to examine the structural and cultural aspects.